Biostimulant induce growth, chlorophyll content and fresh herbage yield of alfalfa (Medicago sativa L.) and variegated alfalfa (Medicago × varia Martyn) plant - Appiah, Ebenezer Ayew; Virág, Csaba István; Kutasy, Erika (Acta Agraria Debreceniensis, 2024)
The use of biostimulants is associated with promoting plant growth by stimulating cell division and improving nutrient availability and uptake. A study was conducted at the University of Debrecen, Hungary, to examine the effect of biostimulants on alfalfa growth, chlorophyll content and fresh herbage yield. The experiment was arranged in a randomised complete block design with three biostimulant treatments plus control replicated three times. Data collected were subjected to analyses of variance using Genstat, where significantly different means were separated at a probability of 5% using the least significant difference. The findings show no different variation in plant height or chlorophyll content (SPAD) throughout the early stages of growth. Nonetheless, a notable impact was noted in the latter stages (28 days after biostimulant treatment application) on the growth of the alfalfa plant. Biostimulant treatments did not had effect on fresh yield for second through fourth cuts, but the fifth cut showed a significant effect, with T1 treatment recording the highest herbage yield of 19745 kg ha-1 followed by T2 (Tricho Immun plus Ino Green) and T3 (Tricho Immun), with yields of 19528 kg ha-1 and 17273 kg ha-1, respectively, while the T0 (control) recorded the lowest herbage yield of 12060 kg ha-1. However, the average mean yield indicated the application of biostimulants significantly increased fresh yield herbage by 20.5%. Correlation coefficient values suggested plant height at both 14 and 28 DAH (days after harvest) strongly correlated with fresh herbage yield (r = 0.7756 and 0.7455) which reflected in the increase in fresh herbage yield. Therefore, our results suggest that the use of biostimulants in alfalfa cultivation holds promise for improving growth and yield potential through their positive effects on chlorophyll content and the growth of alfalfa plant.